2008
DOI: 10.1016/j.drugalcdep.2007.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Alpha synuclein protein levels are increased in serum from recently abstinent cocaine abusers

Abstract: Alpha synuclein is increased in dopamine neurons of cocaine abusers and in rats whose alcohol preference is inbred. Recent studies have shown increased alpha-synuclein protein expression in serum of alcoholic patients that is linked with severity of alcohol craving. The aim of this study was to analyze the serum levels of alpha synuclein in healthy subjects and in recently abstinent cocaine abusers. Alpha synuclein protein expression was measured by enzyme-linked immunosorbent assay in serum specimens obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Methamphetamine can lead to long-lasting decreases in dopamine and serotoninergic function 13 and increases in alpha synuclein expression have been found in the striatum of cocaine addicts postmortem. 14 However, autopsy studies in young cocaine and crystal Meth addicts have not revealed nigral cell loss. 15 Schmidt et al 1 first reported a patient with severe hypokinesia, pseudobulbar palsy, and pyramidal signs after chronic ephedrone use who failed to respond to anti-Parkinsonian medication, and she speculated that the neurological syndrome was caused by manganese accumulation in the brain.…”
Section: Figmentioning
confidence: 99%
“…Methamphetamine can lead to long-lasting decreases in dopamine and serotoninergic function 13 and increases in alpha synuclein expression have been found in the striatum of cocaine addicts postmortem. 14 However, autopsy studies in young cocaine and crystal Meth addicts have not revealed nigral cell loss. 15 Schmidt et al 1 first reported a patient with severe hypokinesia, pseudobulbar palsy, and pyramidal signs after chronic ephedrone use who failed to respond to anti-Parkinsonian medication, and she speculated that the neurological syndrome was caused by manganese accumulation in the brain.…”
Section: Figmentioning
confidence: 99%
“…Overexpressed alpha-synuclein has been observed in midbrain dopaminergic neurons from cocaine abusers, possibly representing a neuroadaptive response to the exposure and potentially exposing them at risk for degenerative changes in dopaminergic neurons [40]. In addition, alpha-synuclein protein levels are increased in serum from recently abstinent cocaine abusers [41]. However, unlike methamphetamine or other amphetamine-type drugs, the available evidence suggests it is unlikely that cocaine confers increased risk of PD [42].…”
Section: - Movement Disorders Associated With Acute Use or Withdrawamentioning
confidence: 99%
“…Likewise, elevated Snca (mRNA, protein) levels were detected in alcoholics [57], and Snca DNA sequence variants have been linked to craving for alcohol in humans [16, 17]. In addition to alcohol-related phenotypes, elevated SNCA levels in midbrain dopaminergic neurons were detected in both cocaine abusers and mice in withdrawal following morphine treatment [58, 59]. Therefore, due to its effects on dopaminergic neurotransmission, Snca is a candidate gene of considerable interest to alcohol-seeking behavior.…”
Section: Corroborative Evidence and Candidate Gene Validationmentioning
confidence: 99%